BEHAVIOR OF PREGNANT WOMEN IN PREVENTING STUNTING AT TERJUN PUBLIC HEALTH CENTER, MEDAN MARELAN DISTRICT - Harahap, Samsidar Rasmi; Nurhikmah, Nurhikmah; B.P, Santri Paramita; Arifa. AF, Nurlaili; Sitepu, Perariken; Paninsari, Debora (Jurnal Kesehatan Saintika Meditory, 2025)
Stunting (stunting) is the occurrence of disturbances in a child's growth and development due to inadequate nutritional intake over a long period of time and recurrent infectious diseases, characterized by the length or height being below the average for children of his age. Prevention of stunting can start when the fetus is in the womb. The aim of this research is to determine the description of the behavior (knowledge, attitudes and actions) of pregnant women in preventing stunting at the ITerjunI Community Health Center, Medan Marelan District, Medan City. Quantitative descriptive research design. The population is 1198 people,targeted by pregnant women at the Terjun Health Center in 2024. The sampling technique is accidental sampling of 92 people using a questionnaire. The research was conducted in December 2024 at the Terjun Community Health Center. Data analysis uses SPSS in the form of I-distribution, Frequency and I-percentagetables for each variable. The results of the research were the age of pregnant women 20-35 years (89.1%), highest school/vocational school education (62%), employment status not working (81.5%), and 2-3 gravida (55.4%). Mothers' knowledge was in the good category as many as 27 people (29.3%), 49 people (53.3%) had sufficient knowledge and 16 people (17.4%) had poor knowledge. Respondents with a Very Good attitude were 59.8%, and the remaining 40.2% had a Good attitude. All respondents (100%) were categorized as having good actions to prevent stunting, including having their pregnancy checked at a health facility (100%), consuming blood supplement tablets (96%), consuming food with animal protein (80%), and having taken part in a class for pregnant women (47%).